ReClaiming participation technology - mediation - collectivity - Denecke, Matthias; Ganzert, Anne; Otto, Isabell 1976-; Stock, Robert 1978- (Media studies, 2016)
This volume unravels the debates on the »Participation Age«: Instead of perpetuating visions of social »all-inclusion« or the »digital divide«, the collection reclaims collectivity as an effect of technological and historical conditions. Thinking of participation both as promise and duty, the contributions analyse the attractions and impositions connected to the socio-technical formation of collectivities. The constraints of participation are addressed by focusing on the mutual shaping of user practices and technological environments. It is hence a relational thinking that allows specifying the manifold interconnections of technology, practices and discourses. Quelle: Klappentext.